THE IMPORTANCE OF MENTAL HEALTH FOUND IN MOVIE ENTITLED KUKIRA KAU RUMAH - Ria Kamilah Agustina (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2022)
This study aims to determine the characterization of the main character named Niskala. In addition, to describe the mental health of the main character. This study used a qualitative descriptive design. The results show that the main character here, named Niskala, has five character points. They are cheerful, warm, introverted, kind and rebellious. Unfortunately, Niskala was also diagnosed with a mental health disorder. This issue is the main message in this film. In conclusion, the main character's personality is cheerful, warm-hearted, introverted, child-friendly and rebellious. Niskala, as the main character, also suffers from mental disorders. There is a lot of evidence to show. The need to heal the patient must be proclaimed. There are many related cases that make the sufferer finally have to end his life. Support from the environment is a joke. Parents, family, close relatives, friends, and even neighbours must unite to uncover this issue so that there is no other Niskala.